KESESUAIAN ALAT BUKTI PETUNJUK PADA PEMBUKTIAN TINDAK PIDANA PORNOGRAFI MELALUI MEDIA ELEKTRONIK - Amadeus Anugrah Dharmawan; Bambang Santoso (Sebelas Maret University, 2023)
his article aims to examine the appropriateness of the evidence used in evidence in trials of criminal acts of pornography through electronic media. This legal writing includes normative legal research, which is prescriptive by using sources of legal materials, both in the form of primary legal materials and secondary legal materials. The technique of collecting legal materials in this research is by means of library research. In writing this law, the author uses an analysis using the syllogism method which stems from the reasoning in the submission of the major premise, namely the Law and Minor Premises of the Decision of the Wates District Court Number 23/Pid.B/2022/Pn.Wat. From these two matters, then a reasoning is drawn regarding suitability of Evidence Guide and proof of expert testimony in proving pornography cases.Based on the results of the research, the Public Prosecutor charged the defendant with alternative subsidiary charges. The evidentiary process at trial shows that the evidence used in proving this crime is in accordance with the provisions of Article 184 of the Criminal Procedure Code regarding evidence. The assessment of the results of evidence has given the Judge confidence that it was the defendant who had committed the crime and obtained the value of expert testimony that supports the evidentiary process in court.